Modifying the Business Financial Plan to Reduce Static Risk Management Costs: Discussion - Rennie, Robert A. (Journal of Finance, 1964)
Robert A. Rennie, Modifying the Business Financial Plan to Reduce Static Risk Management Costs: Discussion, The Journal of Finance, Vol. 19, No. 2, Part 1: Papers and Proceedings of the Twenty-Second Annual Meeting of the American Finance Association, Boston, Massachusetts, December 27-29, 1963 (May, 1964), p. 352